Factors Affecting the incidence of VIA positive at Halmahera Health Care Center in 2018-2019 - Sintia Aprianti; Yunita Dyah Puspita Santik (Jurnal Kesehatan Masyarakat Indonesia, 2021)
Abstract Background : VIA is a simple test with moderate sensitivity and specificity for early cervical lesions screening. The purpose of this study was to determine the relationship between risk factors and the incidence of positive IVA at Halmahera Health Center in 2018-2019.Methods : This type of research is an observational analytic with a case control design. Using purposive sampling technique, the minimum sample size is 68, consisting of 34 cases and 34 controls. Using a questionnaire instrument with interview data collection techniques. Data were analyzed using univariate and bivariate tests using the Chi-Square test with SPSS software.Results : The factors associated with the incidence of positive IVA at Halmahera Health Center were personal hygiene in genital areas (p=0.001, OR = 5.5), history of parity (p= 0.001, OR= 5.9 ) symptoms of vaginal diseases (p=0.003, OR=5.9), and duration of use of hormonal contraceptives (p=0.001, OR=5.25).Conclusion: factors associated with the incidence of positive IVA at Halmahera Public Health Center are personal hygiene of genital area, history of parity, history of genital disease symptoms, and duration of hormonal contraception use.Keywords: Factors, Visual Examination of Acetic Acid, Incidence.